A century of structural and vibrational spectroscopy in vitreous silica: A short review. (26th March 2022) - Hehlen, B.
Abstract: This article reports on more than a century of elastic and inelastic spectroscopies in vitreous silica, the prototypical glass former. The discovery of infrared spectroscopies, Raman and Brillouin scattering, and X‐ray diffraction, opened a new field of science devoted to the description of matter at atomic scale. Theories describing the interaction of radiations with matter rapidely developed, as well as theories based on symmetries for the description of the vibrations. Silica, in its crystalline and vitreous form, has often been the reference material for testing new devices and new theories. As such they were the "witnesses" of the major spectroscopic breakthroughs. Owing to the difficulty to understand disorder, progresses in glasses occurred later than those in crystalline materials. For example, after Zachariasen famous paper in 1932, it was not until the 1960s that 3D random network models were built in support of experimental data. The invention of lasers and the construction of large facilities have also widely extended the range of glass properties accessible using spectroscopies. Concerning vitreous materials in general developments in the last decades of nonconventional techniques as well as numerical tools for the data analysis have opened perspectives for further investigations.